Saponin-based adjuvant uptake and induction of antigen cross-presentation by CD11b+ dendritic cells and macrophages - Lisa GM Huis in ’t Veld; Lenneke AM Cornelissen; Lune van den Bogaard; Marleen Ansems; Nataschja I Ho; Gosse J Adema (npj Vaccines)
Abstract Saponin-based adjuvants (SBAs) distinguish themselves as vaccine adjuvants by instigating a potent activation of CD8+ T cells. Previously, we discovered SBA’s ability to induce cross-presentation in dendritic cells (DCs) leading to CD8+ T cell activation. Moreover, the MHCIIloCD11bhi bone marrow-derived DC (BMDC) subset was identified to be the most responsive DC subset to SBA treatment. To further investigate SBA’s mode of action, labeling of SBAs was optimized with the fluorescent dye SP-DiIC18(3). Efficient uptake of SBAs occurs specifically by MHCIIloCD11bhi BMDCs and bone marrow-derived macrophages (BMDMs) in vitro and cDC2s and macrophages ex vivo. Furthermore, SBAs are primarily taken up by clathrin-mediated endocytosis and uptake induces lipid bodies and antigen translocation to the cytosol in MHCIIloCD11bhi BMDCs and BMDMs. Importantly, BMDMs treated with SBAs exhibit cross-presentation leading to potent CD8+ T cells activation. Our findings explain the potency of SBAs as vaccine adjuvants and contribute to vaccine development.